ANALISIS YURIDIS TERHADAP PEMBAGIAN HARTA PENINGGALAN ALMARHUM LEMAN KEPADA AHLI WARISNYA MENURUT KUHPERDATA (STUDI PUTUSAN PENGADILAN NEGERI MEDAN NOMOR 43/PDT.G/2020/PN.MDN): Juridical Analysis of the Distribution of the Deep Leman’s Assets to His Heirs According to the Court of Data (Study of State Court Decisions Medan Number 43/PDT.G/2020/PN.MDN) - Azzahra, Namira Nur; Suparsetyani, Endang (AMICUS CURIAE, 2024)
Inheritance law contains the determination of who will become the heir. However, the inheritance problem itself cannot be separated from the existence of disputes regarding the distribution of inheritance to the heirs, especially if in the distribution of inheritance there is a will made by the heir, this was also experienced by the late Leman's family, the issues discussed were 1) How distribution of the inheritance of the late Leman to his heirs according to the Civil Code, 2) Whether the contents of the Decision of the Medan District Court Number 43/Pdt.G/2020/Pn.Mdn concerning the distribution of the inheritance of the late Leman to his heirs are appropriate or not according to the Civil Code, conduct research by using analytical descriptive research, where the results of the research were through qualitative and drawing conclusions using the deductive method resulting in the conclusion that 1) The distribution of the assets of the late Leman according to the Civil Code, namely Mrs. Tan Bie Tju (5/8) share, Edison (1/8) share, Verawati (1/8) share, Lilis Leman (1/8) share, and Cindy Chandra do not receive inheritance shares because there is no provision in the Civil Code that regulates the distribution of inheritance to adopted children, 2) The content of the decision of the Medan District Court Number 43/Pdt.G/2020/Pn.Mdn concerning the distribution of the inheritance of the late Lemman to his heirs is not in accordance with the Civil Code.